Impact of air quality model settings for the evaluation of emission reduction strategies to curb air pollution - Bessagnet, Bertrand; Bossioli, Elissavet; Cholakian, Arineh; Vivanco, Marta García; Cuvelier, Kees; Theobald, Mark R.; Gil, Victoria; Menut, Laurent; de Meij, Alexander; Pisoni, Enrico; Thunis, Philippe (2024)
For air quality management, while numerical tools are mainly evaluated to assess their performances on absolute concentrations, this study assesses the impact of their settings on the robustness of model responses to emission reduction strategies for the main criteria pollutants. The effect of the spatial resolution and chemistry schemes is investigated. We show that whereas the spatial resolution is not a crucial setting (except for NO2), the chemistry scheme has more impact, particularly when assessing hourly values of the absolute potential of concentrations. The analysis of model responses under the various configurations triggered an analysis of the impact of using online models, like WRF-chem or WRF-CHIMERE, which accounts for the impact of aerosol concentrations on meteorology. This study informs the air quality modeling community on what extent some model settings can affect the expected model responses to emission changes. We suggest to not activate online effects when analyzing the effect of an emission reduction strategy to avoid any confusion in the interpretation of results even if an online simulation should represent better the reality.
Keywords: Air quality; chemistry; Emission reduction; Meteorology; modeling; Resolution